High speed imaging of a supersonic waterjet flow. Issue 2 (3rd July 2017) - Znamenskaya, I. A.; Koroteeva, E. Y.; Shirshov, Y. N.; Novinskaya, A. M.; Sysoev, N. N.
Abstract: This work studies a jet formation process and a flow developing from a waterjet cutting head. In experiments, the high speed imaging of a supersonic jet (a Photron FASTCAM SA5 camera with a frame rate of 100 kHz) is complemented with the thermographic measurements conducted using an infrared camera FLIR Systems SC7700 with a frame rate of up to 415 Hz. This study aims to provide new knowledge about two-phase flows under extreme conditions, and is of particular importance for waterjet design optimisation.